Outcomes and experiences of families with children with type 1 diabetes on insulin pumps through subsidised pump access programs in Western Australia - Fu, Vivian R.; Irwine, Kathleen; Browne-Cooper, Kirsty; Taplin, Craig E.; Jones, Timothy W.; Davis, Elizabeth A.; Abraham, Mary B. (Frontiers in Endocrinology, 2023)
Introduction: In Australia, access to insulin pump therapy for children with type 1 diabetes (T1D) is predominantly restricted to families with private health insurance (PHI). In an attempt to improve equity, additional subsidised pathways exist which provide pumps to families with reduced financial resources. We aimed to describe the outcomes and experiences of families with children commenced on pumps through these subsidised pathways in Western Australia (WA). Methods: Children with T1D in WA who did not have PHI and received pumps through subsidised pathways between January 2016 and December 2020 were included. Study 1 was designed to review glycaemic outcome. A retrospective analysis of HbA1c was conducted in the whole cohort and in children who commenced pump after 12 months to exclude the impact of the partial clinical remission phase following diagnosis. HbA1c at baseline, six, 12, 18 and 24 months after pump initiation were collected. Study 2 was designed to review experiences of families commenced on pumps through subsidised pathway. A questionnaire designed by the clinical team was distributed to parents via an online secure platform to capture their experiences. Results: Of the 61 children with mean (SD) age 9.0 (4.9) years who commenced pump therapy through subsidised pump programs, 34 children commenced pump therapy after one year of diagnosis of T1D. The median (IQR) HbA1c (%) in 34 children at baseline was 8.3 (1.3), with no statistically significant change from baseline at six months [7.9 (1.4)], 12 months [8.0 (1.5)], 18 months [8.0 (1.3)] or 24 months [8.0 (1.3)]. The questionnaire response rate was 56%. 83% reported intention to continue pump therapy, however 58% of these families did not have avenue to acquire PHI. Families expressed inability to procure PHI due to low income and unreliable employment and remained largely unsure about the pathway to obtain the next pump. Discussion: Children with T1D who commenced insulin pump therapy on subsidised pathways maintained glycaemic control for two years, and families favoured pumps as a management option. However, financial limitations persist as a significant barrier to procure and continue pump therapy. Pathways for access need to be assessed and advocated.